Manajemen Pendidikan Nonformal dan Karakter Islami di Rumah Tahfiz Ahlul Qur’an Assyafani : Penelitian - Ega Putri Handayani; Martin Kustati; Nana Sepriyanti (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2025)
Islamic character education has an important role in forming a generation essential role in shaping a generation that is not only intellectually intelligent, but also spiritual strong. This article discusses the management of non-formal education in implementing Islamic character education at the Rumah Tahfiz Ahlul Qur’an Assyafani, Gantung Ciri, Solok. This research used a qualitative approach with a case study method. Data collection techniques are carried out through observation, interviews and included observation, interviews and documentation. The research results show that the institution includes program planning, implementation of tahfiz learning, as well as evaluation based on Islamic values. Values such as honesty, responsibility, and love of the Qur’an are Instilled through example and practice. Supporting factors for implementation include management commitment, community support, and the religious atmosphere of the institution. It is hoped that this article can be a reference for manager of non formal institutions in implementing Islamic character education effectively.